Cangrelor: an emerging therapeutic option for patients with coronary artery disease. (May 2014) - Kubica, Jacek; Kozinski, Marek; Navarese, Eliano Pio; Tantry, Udaya; Kubica, Aldona; Siller-Matula, Jolanta Maria; Jeong, Young-Hoon; Fabiszak, Tomasz; Andruszkiewicz, Anna; Gurbel, Paul Alfred
Abstract Objectives: To perform a systematic up-to-date review and critical discussion of potential clinical applications of cangrelor based on its pharmacologic properties and the main findings from randomized clinical studies. Methods: A database search (PubMed, CENTRAL and Google Scholar) by two independent investigators, including proceedings from scientific sessions of ACC, AHA, ESC, TCT and EuroPCR, from January 1998 through December 2013. Results: Cangrelor is a potent, intravenous, direct-acting P2Y12 antagonist with rapid onset and quickly reversible action. In contrast to ticagrelor, cangrelor's interaction with thienopiridines requires termination of cangrelor infusion before switching to clopidogrel or prasugrel. According to randomized trials, a cangrelor–clopidogrel combination is relatively safe and more effective than the standard clopidogrel regimen in both urgent and elective percutaneous coronary intervention (PCI) settings, with the advantage of this drug combination fully evident when the universal definition of myocardial infarction is applied. In contrast to available antiplatelet drugs with delayed onset and offset of action, its favorable properties make cangrelor a desirable agent for ad hoc elective PCI, high risk acute coronary syndromes treated with immediate coronary stenting and for bridging those surgery patients who require periprocedural P2Y12 inhibition. Current evidence on cangrelor therapy is limited by the lack of adequately powered studies assessing cangrelor co-administration either with prasugrel or ticagrelor, suboptimal design of some of the trials favoring cangrelor, potentially attenuated benefits with modern stent design, and finally, by the lack of survival advantage. Conclusions: With its pharmacokinetic and pharmacodynamic advantages, allowing consistent and strong P2Y12 inhibition, and with its rapid onset and swift reversal of action devoid of need for an antidote, cangrelor might improve clinical outcomes in clopidogrel-treated patients by reducing ischemic events, while maintaining a favorable safety profile. However, further studies, addressing the safety and efficacy of cangrelor on top of novel oral P2Y12 inhibitors, are warranted.